2018
DOI: 10.1016/j.nedt.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Using reusable learning objects (RLOs) in wound care education: Undergraduate student nurse's evaluation of their learning gain

Abstract: These findings provide evidence that the use of RLOs for both knowledge-based and performance-based learning is effective. RLOs when designed using clinically real case scenarios reflect the true complexities of wound care and offer innovative interventions in nursing curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…"); and T5, criticism (e.g., "Could be more interactive."). Their qualitative data were generally positive and in agreement with other studies, which reported students' comments (Redmond et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…"); and T5, criticism (e.g., "Could be more interactive."). Their qualitative data were generally positive and in agreement with other studies, which reported students' comments (Redmond et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The flexibility of learning (also referred to as independent learning) is identified as a major advantage of using RLOs, not only in this study but also by other studies (Redmond et al, 2018). In this study, the RLOs were administered in the presence of an instructor and laboratory teaching assistant, who enhanced the learning process by responding to questions and providing expert knowledge (Grunwald, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Constructivism learning fosters the capability to manipulate and interpret information as well as increasing confidence in meeting competency [35,36]. Participants were exposed to a learning environment that invited participants to use information gained from the course and then interpret that information regarding dementia care in their own working environment (eg through the weekly chat-room discussions).…”
Section: Practice Improvementmentioning
confidence: 99%